TAMBANG RAKYAT, BERKAH ATAU MUSIBAH? (STUDI TENTANG TAMBANG EMAS RAKYAT DI GUNONG UJEUN KABUPATEN ACEH JAYA) - Aminah Aminah (Jurnal Public Policy, 2017)
This study aims to explain the gold mining in Gunong Ujeun, Aceh jaya by using the theories of Thomas Homer-Dixon of  the environmental scarcity, whether  in Gunong Ujeun mining can be categorized as a blessing or a disaster with a view of reality and phenomena  that exist  in  the field.  The  data  in  this  research was  obtained  through  literature  (library  research)  and  field research. The  results  showed  that  small-scale  gold mining  in  the  region Gunong Ujeun has many benefits, it is a blessing bestowed by the Almighty to the people, especially for people who do the mining. Since 2008 has been a lot of things are changing in the region District of Krueng Sabee, ranging from forests to watersheds in the river. The destruction of the forest will be an impact on other natural  resources  such as  soil cycles are no  longer  fertile, discoloration and quality of water, as well as damage to the fish that were in the river will die, and as a result of toxic mercury wastes are poured into the river. This caused conflict among the community. It is is a horizontal conflict   between migrant and  local communities. The cause of it, namely (1) frequent flooding aftermath of the mining (2) more difficult to get fresh fish and   the water has been  contaminated with mercury  and  cyanide.  (3)  government  agency  that  is  less  concerned with the environment (4) Control of natural resources by immigrant communities.  Keywords: Peoples Mining, conflict, environmental degradation.